PERANCANGAN SISTEM INFORMASI GEOGRAFIS PARIWISATA BERBASIS WEB DI DINAS KEPEMUDAAN DAN OLAHRAGA DAN PARIWISATA KABUPATEN KEBUMEN - Waluyo, Ari; Santoso, Satria Budi (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2018)
The purpose of this research is to know the geographic information system of tourism that is in Dinas Kepemudaan dan Olahraga dan Pariwisata Kebumen Regency and develop it Research methods used by doing observationin Dinas Kepemudaan dan Olahraga dan Pariwisata Kebumen Regency, then proceed with the system development method. the research method used is by the method of SDLC (System Development Life Cycle). By using the Software Notepad ++ to build tourism Geographical Information System web-based. PHP as a programming language, MySQL as the database server and the design of the map using the Google Maps API. The object-oriented approach that is used UML (Unified Modeling Language) can explain the flow of the existing system. Dinas Kepemudaan dan Olahraga dan Pariwisata Kebumen Regency has been doing promotion through mass media such as newspapers and brochures in the delivery of information. But the way is not enough to inform tourism and places of attractions. It is therefore through the design of Geographical information system of tourism was able to resolve the issue. After the results of the study of geographic information systems is expected delivery of tourism information becomes more widespread, and the tourists could be quick and precise in finding information a tourist want to visit.